Cognitive behavioral therapy: A valuable intervention in the autistic universe (International Seven Journal of Health Research, 2024)
The scope of this article is to understand intervention models in the cognitive and behavioral approach with learners with ASD, with the aim of expanding their skills and capabilities for a life with greater autonomy. based on analyzing the evolution of patients with the disorder within the process of cognitive-behavioral therapy, in order to combine therapeutic actions with the use of specific techniques, highlighting changes and meanings outlined by multiple theorists. where we envision that Cognitive Behavioral Therapy (CBT) , as an intervention in cases of patients with impairments of the most varied levels of support, indicated significant evolution, helping to validate this approach as being of great value in the evolution of clinical conditions of people within the spectrum